Isolation of marine bacteria with bioremediation properties from the culture water of Tiger grouper (Epinephelus fuscoguttatus) - Khairuddin Mohd Amin.
An experiment was conducted to isolate bacterial bioremediator from the culture water of Tiger Grouper (Epinephelus fuscoguttatus). In this study, the potential of the bacteria as ammonia degraders were investigated. This was done through enrichment assay using ammonium sulphate as carbon source. The bacteria were grown in minimal medium and sodium chloride. Through this assay, three distinct bacteria were isolated. Using the total ammonia-nitrogen (TAN) analysis, all three bacteria were able to degrade ammonium sulphate up to 0.04 ppm compared to the control of 0.54 ppm. All three bacteria were found to be Gram-positive bacteria by its distinctive purple color in Gram-staining method. Based on result, it can be concluded that the marine bacteria isolated from the culture water of Tiger grouper have the potential as bioremediator agent in aquaculture.